Improving the topics of General schools in the direction of “fundamentals of life safety”, integrated into the composition of the subjects technologyas (Eurasian Scientific Herald, 2024)
The incorporation of life safety fundamentals into technology subjects in general schools is vital for equipping students with essential skills and knowledge. This article explores how life safety principles can be effectively integrated into technology curricula, enhancing students' awareness and preparedness for real-life situations. It examines the current literature on the subject, proposes methods for integration, discusses the results of implementation, and offers conclusions and suggestions for future improvements